THE INFLUENCE OF WORK LIFE BALANCE AND INTERPERSONAL COMMUNICATION ON JOB SATISFACTION IN TEBING TINGGI POLRES MEMBERS - Muhammad Rasyidin; Sjahril Effendy P; Rahmi Lubis (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This study aims to determine the effect of WLB and Interpersonal Communication on Job Satisfaction among members of the Tebing Tinggi Police. The population of this study were 124 members of the Tebing Tinggi Police. Sampling of this study by total sampling technique, where the entire population is a sample of 124 people. This research uses quantitative methods. The measurement tools used are the WLB scale, the Interpersonal Communication scale and the Job Satisfaction scale. Data analysis using multiple linear regression test. The results of this study indicate that (1) There is an influence of WLB on Job Satisfaction in members of the Tebing Tinggi Police, where the significance value is 0.000, namely 0.05, so the hypothesis is rejected.